ANALISIS PRAKTIK PERLOMBAAN MEMANCING PERSPEKTIF HUKUM EKONOMI SYARI’AH: (Studi Kasus di Kolam Pancing Selma Dsn. Sedati Ds. Kauman Kec. Ngoro Kab. Jombang) - Amzahril Azis; Syai’in Syai’in (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Amzahril Azis 2025. Analysis of Fishing Competition Practices from the Perspective of Sharia Economic Law (Case Study at Selma Fishing Pond, Sedati Hamlet, Kauman Village, Ngoro District). Thesis, Sharia Economic Law Study Program, Faculty of Islamic Studies, Hasyim Asy’ari Tebuireng University Jombang, Advisor; Syai’in, M.Sy.The author conducted a research titled